Evidências de validade do AAQ-2 (Questionário de Aceitação e Acão II) em profissionais da Atenção Primária à Saúde no Brasil e correlações com ansiedade, mindfulness e autocompaixão - Otero, Tatiana Berta [UNIFESP] (2016)
Introduction: The psychological flexibility has been considered an important predictor of quality of life. Experiential avoidance, in turn, is related to various diseases. Health indicators on workers of Primary Care Services indicate high levels of burnout and mental disorders in the category. Objectives: This study evaluates the internal consistency and construct validity of the factors of the Brazilian version of AAQ-2 scale (Acceptance and Action Questionnaire), correlating them with measures of anxiety, mindfulness and self-compassion in this population. Method: The study, correlational cross-sectional, with measurements obtained by self-report technique consisted of a sample universe of 407 PHC professionals and used sociodemographic questionnaire and the AAQ-II scales, HADS, FFMQ and SCS as instruments. Demographic data were analyzed using descriptive statistics. Confirmatory Factor analysis were used to analyze the dimensionality of AAQ-II and the internal consistency was examined based on the Cronbach α coefficient. Correlations Pearson's r were made between the AAQ-II factors and the HADS scales and SCS to assess the correlations. Results: The mean age of these workers is 41, 12 (10,10) years, 84.5% were female, 70.3% live with a partner. With regard to occupation, 17.7% are physicians, nurses 25.1% and 57.2% other (community workers, dentists etc). The category study reported high levels of anxiety and depression related to psychological inflexibility, as measured by AAQ-II. Conclusions: The AAQ-II seems to be a valid instrument in the population of Primary Care Providers in Brazil, with good internal consistency.There is a strong positive correlation between scores of anxiety / depression and psychological inflexibility, as well as in self-compassion and mindfulness.